Interactions between quantum emitters in the presence of plasmonic nanostructures - Karanikolas, Vasilios D. (Trinity College (Dublin, Ireland). School of Physics, 2016)
In this thesis the spontaneous emission, of a single quantum emitter, and the energy transfer, between a pair of quantum emitters, rates are investigated in the presence of conducting nanostructures. The competition between these two rates leads to the introduction of the energy transfer efficiency. Metallic and graphene nanostructures are investigated. The excitation of surface plasmon modes, hybrid modes of the conduction band electrons and the electromagnetic field, is crucial for enhancing the spontaneous emission and energy transfer rates, compared with their free space values. The near field of the quantum emitters can directly excite the surface plasmon modes. The surface plasmon wavelengths depend on the shape and material properties of the nanostructures. The spectral and distance dependences of the spontaneous emission and energy transfer processes are studied. It is of particular interest, from the point of view of applications, to be able to manipulate the light at nanometer distances. In particular, metallic multilayer planar and cylindrical geometries are investigated. The noble metals, Ag and Au, are used as the conducting metallic medium. Their surface plasmon wavelengths lie in the visible part of the spectrum. For planar geometries the distance and spectral dependences of the spontaneous emission rate are analyzed, and their connection with the dispersion relation, the propagation length and penetration depth of the surface plasmon mode is pointed out. For the dielectrically coated cylinder the influence of the coating on coupling with the near field of the quantum emitters and excitation of the surface plasmon mode, which subsequently leads to larger interactions distances, is presented. The energy transfer efficiency is influenced by the overlap of the emission spectrum, of the donor quantum emitter, and the absorption spectrum, of the acceptor quantum emitter, with the surface plasmon resonance wavelength. Then, the interaction distance between the quantum emitters can be enhanced compared with their free space value. Tuning the surface plasmon wavelength to the emission wavelength of the donor via the geometrical and material parameters of the coated cylinder allows control of the energy transfer efficiency. Furthermore, a graphene monolayer and graphene nanodisk are considered as conducting media supporting surface plasmon modes. Their surface plasmon wavelengths lie in the near to far infrared part of the spectrum. For the gated graphene monolayer the influence of the propagation length and penetration depth on the energy transfer rate is presented. The graphene monolayer can support efficient coupling between the quantum emitters up to distances of 300 nm when the quantum emitters are on resonance with the surface plasmon mode. For the graphene nanodisk the surface plasmon frequencies are investigated. Different transition dipole moments of the quantum emitters excite different sets of resonances. When the emission wavelength of the quantum emitter matches the resonance frequencies, the spontaneous emission and energy transfer rates are enhanced by several orders of magnitude compared with their free space values. The distance dependence of the energy transfer rate between a pair of quantum emitters, placed perpendicularly to the graphene nanodisk plane, is studied and is found that it depends on the geometrical characteristics of the graphene nanodisk in contrast with the graphene monolayer where the penetration depth, of the surface plasmon mode, dominates.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin